The LEGO Mindstorms EV3 idea book : 181 simple machines and clever contraptions - Isogawa, Yoshihito, 1962- (No Starch Press, Inc., 2015)
This book explores dozens of creative ways to build amazing mechanisms with the LEGO MINDSTORMS EV3 set. Each model includes a list of the required parts, minimal text, and colorful photographs from multiple angles so you can re-create it without the need for step-by-step instructions. You'll learn to build cars with real suspension, steerable crawlers, ball-shooters, grasping robotic arms, and other creative marvels. Each model demonstrates simple mechanical principles that you can use as building blocks for your own creations. Every part you need to build these machines comes in one LEGO set (#31313).